DESIGN COOLING TOWER OF THE MECHANICAL DRAFT TYPE COUNTER FLOW TO ACHIEVE AMBIENT TEMPERATURE - Setiawan, Angga Tegar; Fahrul, Fahrul; Arohman, Abdul Wahid; Anugrah, Fahmi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
The application of cooling towers in various industries has been widely used to meet needs. The main purpose of this study is to create an effective cooling tower in the water-cooling process by using the counter flow principle to meet the need to reduce the water temperature of the cooling system in transformers and holders of electric arc furnaces. The method used in the design and construction of the Cooling tower Mechanical draft Type Counter Flow tool includes the stages of planning, designing, making trials, and processing data. The planning stage involves gathering literature, searching for the best design, and determining the design plan. The design stage includes the design of the tool using Computer Aided Design (CAD) and the selection of materials to be used. The manufacturing stage involves assembling machine components into the desired design machine. Heat transfer analysis is also carried out to discover the heat transfer phenomenon. The test results show that the temperature data on the Thot, water cooling tower is 65,9 oC, Tcavity is 48 oC, Twater column is 28 oC, and Tcold is 26,8 oC. So that the design of the tool shows a decrease in temperature at each stage, including Tcavity is 21 oC, T water column is 20 oC, and T tank is 1,2 oC. The mini cooling tower achieved a high cooling range of 35,9 oC and a low approach of 3,2 oC. It can reduce the water temperature from the cooling process in the transformer and holder electric arc furnace. The design has released the hot water temperature from 65,9 oC to 26,8 oC. The design of the tool has succeeded in releasing heat as much as 61,4 kJ/s. Thus, the water from the cooling process can be effectively reused as a cooling medium, offering a practical and efficient solution for enhancing sustainability in small to medium-scale industrial cooling processes.